PERENCANAAN TEMPAT PENGOLAHAN SAMPAH (TPS) 3R KECAMATAN BANJABARU UTARA KOTA BANJARBARU - Rijal, Muhammad Nor; Firmansyah, Muhammad; Abdi, Chairul; Khair, Riza Miftahul (Prodi Teknik Lingkungan Fakultas Teknik Universitas Lambung Mangkurat, 2024)
Waste is the rest of human daily activities and / or natural processes in solid form. Waste can have a very bad impact on people's health and environment if it cannot be addressed. The waste problem must be handled appropriately. One alternative to improving waste management is by replacing or implementing an existing waste treatment site with a 3R (reduce, reuse, and recycle) based waste treatment site. The amount of waste generation is directly proportional to population growth. North Banjarbaru is one of the sub-districts in Banjarbaru City with an area of 26,855 km2. North Banjarbaru District has a population of 53,770 people (as of 2021) and has a population growth rate of 1.31% annually, North Banjarbaru is the district with the densest population density of 2,162 people/km2. The data processing method used in planning consists of site selection, population projection calculation, waste generation calculation, mass balance calculation, land/space needs calculation, and 3R TPS floor plan layout. The logarithmic method is used for the calculation of population projections and waste generation in TPS 3R planning because it has the best correlation coefficient value and standard deviation. The total population of waste generation in the planning year (2031) is 65.595 people and 28,206 tons/day. The planning location is located on Jl. Pd. Sejahtera, North Loktabat Village. The land area required for this plan is 365.3 m2. Keyword: waste, population, waste generation, TPS 3R planning